Factors associated with transcendental meditation practice in older people - Daniel Vicentini de Oliveira; Sônia Maria Marques Gomes Bertolini; Ellis Gilson Chatalov; Maura Fernandes Franco; Maria do Carmo Correia de Lima; Gabriel Lucas Morais Freire; Rogéria Vicentini de Oliveira; José Roberto Andrade do Nascimento Júnior (Hospital de Clínicas de Itajubá, 2020)
Aims: To evaluate factors associated with the practice of transcendental meditation (TM) in the elderly. Methods: Cross-sectional study, with the inclusion of 113 older adults and women, 60 of them practitioners and 53 non-MT practitioners. A semi-structured questionnaire was used as an instrument, composed of sociodemographic, health and TM practice data. Data analysis was performed using the chi-square test and binary logistic regression. Results: The average age of practitioners was lower than that of non-practitioners (63.7 ± 4.0 vs. 69.1 ± 6.6 years). Most of the sample had completed higher education (f = 45; 75%; p = 0.001) and received more than three minimum wages (f = 40; 67.8%; p = 0.001). In the group of TM practitioners there was a greater proportion of individuals with excellent / good self-perceived health (91.7% vs 77.4%; p = 0.034), and less hospitalization in the last semester (5% vs 24.5 %; p = 0.003). Older adults who denied hospitalization or the presence of diabetes mellitus (DM) presented, respectively, 5.7 (95% CI OR 1.1 - 28.9) and 4.9 (95% CI OR 1.3 - 19.2) times chance to practice MT. The practice of TM is 80% more likely to be practiced by older adults with better self-perceived health (OR 0.17; 95% CI 0.03 - 0.96). Conclusion: The practice of a holistic activity such as TM is associated with better self-perceived health than older adults of the same age, and less chance of hospitalization in the last semester and the presence of DM.